POVERTY IN URBAN AND RURAL AREAS - Wahyudi, Drajat; Nabilah, Nada; Yulianti, Syifa Aulia; Sholihah, Vinly (LPPM Universitas Bina Bangsa, 2024)
Poverty is a complex social issue that affects many aspects of human life. This study aims to analyze the factors contributing to poverty in urban and rural areas, as well as its impact on social, economic, and environmental life. The research method used is a qualitative approach with a comparative analysis of poverty in urban and rural areas. The results of the study indicate that poverty in urban areas is primarily influenced by urbanization, unemployment, and income inequality, while in rural areas, it is more influenced by dependence on the agricultural sector, inadequate infrastructure, and low levels of education. The impacts of poverty are visible in various aspects, ranging from education, health, to excessive exploitation of natural resources. Furthermore, this study also found significant differences in the severity of poverty and the necessary solutions between urban and rural areas. Poverty alleviation requires a locally-based approach that involves cooperation between the government, NGOs, and the community, with a focus on improving access to education, health, and economic empowerment.